2022
DOI: 10.3389/fpls.2022.1018029
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analysis of genomes and functional genomics of orchid using cutting-edge high-throughput sequencing

Abstract: High-throughput sequencing technology has been facilitated the development of new methodologies and approaches for studying the origin and evolution of plant genomes and subgenomes, population domestication, and functional genomics. Orchids have tens of thousands of members in nature. Many of them have promising application potential in the extension and conservation of the ecological chain, the horticultural use of ornamental blossoms, and the utilization of botanical medicines. However, a large-scale gene kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 164 publications
0
7
0
Order By: Relevance
“…The bHLH-MYC_N domain contains JID and TAD, which are responsible for the binding of JAZ to MYC2 and the transcriptional activation of MYC-targeted genes, respectively. DhMYC2 contains GDG motifs, suggesting their ability to bind JAZ proteins ( Song et al., 2022b ). The presence of RA[K/L]QAQ motifs in DhMYC2 suggests that it is a canonical MYC2 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bHLH-MYC_N domain contains JID and TAD, which are responsible for the binding of JAZ to MYC2 and the transcriptional activation of MYC-targeted genes, respectively. DhMYC2 contains GDG motifs, suggesting their ability to bind JAZ proteins ( Song et al., 2022b ). The presence of RA[K/L]QAQ motifs in DhMYC2 suggests that it is a canonical MYC2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…In normal growth conditions, JA is at a low level; when subjected to external stress, the JA content of the seedlings rapidly increased, which activates JA-responsive genes to increase resistance to environmental stimuli ( Zhu et al., 2017 ). JA also induced the expression of key enzymes in the terpenoid biosynthesis pathway and raised terpene alkaloid content in a short period of time ( Song et al., 2022b ). The bHLH genes have been widely investigated in both model plants and medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, DoWRKY26 shared a high level of homology with AtWRKY18, 40, and 60; hence, it was suggested that WRKY26 might be involved in the transcriptional regulation of secondary metabolite biosynthetic genes (Figure 8). Gene duplications are critical to the rapid expansion of the genome and the evolution of gene families (Song et al, 2022c). Polyploidy drives species adaption, genetic diversity, and genome evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplications are critical to the rapid expansion of the genome and the evolution of gene families ( Song et al, 2022c ). Polyploidy drives species adaption, genetic diversity, and genome evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, orchids cannot survive without mycorrhizal fungi (Rasmussen & Rasmussen, 2014). In recent years, there has been a growing interest in the genomics of orchids and ORM fungi to unravel the genetic mechanisms underlying orchid‐fungal interactions and the specificity of these symbiotic relationships (Chen et al ., 2022; Song et al ., 2022). The genomes of several orchid species (Cai et al ., 2015; Zhang et al ., 2016, 2017; Yang et al ., 2021; Jiang et al ., 2022; Li et al ., 2022) have been sequenced.…”
Section: Harnessing Genomics To Enhance Our Understanding Of the Deve...mentioning
confidence: 99%